Simultaneous Measurement of Distributed Temperature and Strain through Brillouin Frequency Shift Using a Common Communication Optical Fiber - Leijun Hu; Liwen Sheng; Jisong Yan; Ligong Li; Ming Yuan; Fude Sun; Fushun Nian; Long Li; Jiaqing Liu; Shuai Zhou; Zhiming Liu (International Journal of Optics)
A multiparameter Brillouin fiber-optic sensor for distributed strain and temperature information measuring based on spontaneous scattering in a common communication optical fiber (the G. 652. D commercial fiber) is presented and experimentally demonstrated. Benefiting from the difference of the temperature and strain sensitivity from different Brillouin peaks with different acoustic modes, our proposed sensing configuration can be used to distinguish ambient temperature and applied strain at the same time, which is an excellent candidate to address the problem of cross-sensitivity in the classical Brillouin system. In the experimental section, using a 21.8 km sensing length of communication optical fiber, a temperature accuracy of 1.13°C and a strain accuracy of 21.46 με are obtained simultaneously. Considering the performance we achieved now, the proposed innovation and experimental setup will have some potential applications in the field of fiber sensors.